2016
DOI: 10.1116/1.4971990
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the dimers and tetramers of metal amidinate atomic layer deposition precursors upon adsorption on silicon oxide surfaces

Abstract: The gas-phase structure of three copper amidinate compounds, copper(I)-N,N′-di-sec-butyl-acetamidinate (1), copper(I)-N-sec-butyl-2-iminopyrrolidinate (2), and copper(I)-N-tert-butyl-5,5-dimethyl-2-iminopyrrolidinate (3), and their initial adsorption on silicon oxide surfaces, were characterized by a combination of experimental measurements and density-functional theory (DFT) calculations. These compounds have previously been shown to crystallize in dimeric or tetrameric form, and liquid-injection field desorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 13 publications
(52 citation statements)
references
References 52 publications
4
46
2
Order By: Relevance
“…Our previous work had indicated that these oligomers, typically dimers, are quite stable: they are well known to form in the solid phase [9,10,11] and are also thermodynamically favored in the gas phase (the DFT calculations in those reports did not include van der Waals interactions, but the new calculations reported here, which do, corroborate the general trends identified before) [19,22]. Moreover, we found that in the dimer of Cu(I)-(2-sec-butylimino)-pyrrolidinate, the copper ions appear to be sheltered to a sufficient degree that, on silica surfaces at least, the first interaction is not via the metal center but rather through one of the nitrogen atoms [19]. We speculate that such initial interaction may promote subsequent surface chemistry, leading to the decomposition of the ligands not foreseen when these precursors were designed for film growth applications.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Our previous work had indicated that these oligomers, typically dimers, are quite stable: they are well known to form in the solid phase [9,10,11] and are also thermodynamically favored in the gas phase (the DFT calculations in those reports did not include van der Waals interactions, but the new calculations reported here, which do, corroborate the general trends identified before) [19,22]. Moreover, we found that in the dimer of Cu(I)-(2-sec-butylimino)-pyrrolidinate, the copper ions appear to be sheltered to a sufficient degree that, on silica surfaces at least, the first interaction is not via the metal center but rather through one of the nitrogen atoms [19]. We speculate that such initial interaction may promote subsequent surface chemistry, leading to the decomposition of the ligands not foreseen when these precursors were designed for film growth applications.…”
Section: Discussionsupporting
confidence: 84%
“…We do not have at present an interpretation of these observations or a full assignment of all of the amus detected, but speculate that perhaps the species desorbing at 350 K is a dimer where some skeletal rearrangement has taken place. Another possibility is that one of the peaks may correspond to a dimer and the other to a tetramer, as the two are not too far in energy [19]. It is difficult to settle this point with the available data.…”
Section: Low-temperature Tpdmentioning
confidence: 99%
See 3 more Smart Citations